2011
DOI: 10.1007/s00167-011-1808-2
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps femoris muscle function prior and after total knee arthroplasty in women with knee osteoarthritis

Abstract: Prospective comparative study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 38 publications
(84 reference statements)
1
30
1
1
Order By: Relevance
“…This is surprising given that subjects with knee osteoarthritis do present with significant muscle impairments that affect physical function [54] as well as wide variations in whole muscle contractile kinetics [55] . Rate of force development [13] , and effusion, a determinant of muscle function in knee osteoarthritis, is also not well correlated with findings in the context of the present topic [45] . Hence, although muscle strength is often a target of therapy for knee osteoarthritis, there is no direct information from current studies that this approach will be universally desirable or effective.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This is surprising given that subjects with knee osteoarthritis do present with significant muscle impairments that affect physical function [54] as well as wide variations in whole muscle contractile kinetics [55] . Rate of force development [13] , and effusion, a determinant of muscle function in knee osteoarthritis, is also not well correlated with findings in the context of the present topic [45] . Hence, although muscle strength is often a target of therapy for knee osteoarthritis, there is no direct information from current studies that this approach will be universally desirable or effective.…”
Section: Discussioncontrasting
confidence: 56%
“…To this end more stringent research designs with clear inclusion and exclusion criteria are desirable to tease out possible pathogenic or confounding factors in gait and electromyographic studies such as disease stage [35,44] , the presence of instability [44] , effusion [45] , proprioception abnormalities [47] , excess body weight [76,77] fatigue [78] , instability [79] , stiffness [80] , inflammatory cytokines [81] , gamma-loop dysfunction [82] , or related muscle forces at the knee during gait [83] . Whether rate of force development, muscle endurance and/or muscle power, muscle imbalance, muscle force steadiness or neuromuscular efficiency are more profound functional determinants than strength [13,31,41,80,[84][85][86] should also be examined. Which interventions produce the best functional outcomes and why should be examined as well to better understand the muscular mechanisms underpinning functional weightbearing activities in patients with varying degrees of knee joint osteoarthritis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were reported by Berth et al (2002) and Yoshida et al (2008), who investigated muscle strength from 1 to 3 years after TKA and observed an increase relative to preoperative values. However, Vahtrik et al (2012), who investigated muscle strength at 3 and 6 months after TKA, found that postoperative muscle strength was lower than the preoperative value. Thus, it may be that after TKA surgery, the recovery and improvement of muscle strength can take more than 6 months.…”
Section: Discussionmentioning
confidence: 98%
“…However, full recovery of muscle strength after TKA is uncommon (Berth et al 2002, Valtonen et al 2009, Maffiuletti et al 2010, Vahtrik et al 2012). …”
mentioning
confidence: 99%